Well Known and Unknown Asthma Phenotype: Allergic Asthma - Ayse Bilge Öztürk; Sadi Can Sönmez; Emre Göğebakan; Leyla Pur Özyiğit; Benan Çağlayan (European Medical Journal Allergy & Immunology, 2019)
Allergic asthma is the most common phenotype of asthma and presents with various clinical subtypes and clusters, emphasising the importance of personalised treatments in its management. The disease has an IgE-mediated inflammatory course that may be triggered by many agents, such as pollens and nonsteroidal anti-inflammatory drugs. The allergic asthma patients are relatively young, with early-onset asthma and frequent exacerbations. The primary goal of this literature review is to provide a deeper insight into different patient groups and allergic asthma phenotypes, as well as to discuss treatment options accordingly. Triggering factors and clinical presentation of patient groups are also covered in this study.